2018
DOI: 10.1111/aos.13806
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y treatment induces retinal vasoconstriction and causes functional and histological retinal damage in a porcine ischaemia model

Abstract: In seeming contrast to previous in vitro studies, intravitreal NPY treatment caused functional and histological damage compared to vehicle after a retinal ischaemic insult. Furthermore, we showed for the first time that NPY induces Y1- and Y2- but not Y5-mediated vasoconstriction in retinal arteries. This constriction could explain the worsening in vivo effect induced by NPY treatment following an ischaemic insult and suggests that future studies on exploring the neuroprotective effects of NPY might focus on o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…In contrast, recent publications suggest NPY does not exert a protective effect in the retina and that NPY shows no association at gene level (SNP in NPY2R gene) in patients with diabetes . These reports utilize notably different models, addressing different questions but taken together, may suggest that NPY signalling is context‐dependent, with the potential to exert both beneficial neuroprotective and negative effects.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In contrast, recent publications suggest NPY does not exert a protective effect in the retina and that NPY shows no association at gene level (SNP in NPY2R gene) in patients with diabetes . These reports utilize notably different models, addressing different questions but taken together, may suggest that NPY signalling is context‐dependent, with the potential to exert both beneficial neuroprotective and negative effects.…”
Section: Discussionmentioning
confidence: 89%
“… Although no direct evidence in retinal endothelium, NPY can induce migration and proliferation of endothelial cells via its receptors and regulate their function . Conversely, a recent study demonstrates that NPY treatment in a model of acute retinal ischaemia reduced retinal function and tissue damage …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Christiansen and colleagues tested the effects of intravitreal NPY treatment in a porcine model of acute retinal ischemia and found that it only enhanced ischemic damage ( Christiansen et al, 2018b ). These observations are markedly important as they contradict earlier results where NPY treatment has been found to convey neuroprotective effects or at least significant change in retinal health could not be observed following treatment (results from cell cultures by Alvaro et al, 2008 ; earlier experimental work reviewed by Santos-Carvalho et al, 2014 ; and a study conducted on rat retinas by Martins et al, 2015 ).…”
Section: Metabolic Retinal Diseases: Pathology and Neuropeptidesmentioning
confidence: 99%
“…These observations are markedly important as they contradict earlier results where NPY treatment has been found to convey neuroprotective effects or at least significant change in retinal health could not be observed following treatment (results from cell cultures by Alvaro et al, 2008 ; earlier experimental work reviewed by Santos-Carvalho et al, 2014 ; and a study conducted on rat retinas by Martins et al, 2015 ). Christiansen and colleagues argue that the damaging effect could have been masked in the ex vivo models used in earlier studies as NPY has been demonstrated to cause vasoconstriction in the retinal arteries ( Prieto et al, 1995 ; Christiansen et al, 2018b ). Regardless, NPY was shown to play no role in pathological retinal neovascularization in the OIR mouse model ( Schmid et al, 2012 ).…”
Section: Metabolic Retinal Diseases: Pathology and Neuropeptidesmentioning
confidence: 99%
“…In particular, intravitreal injection of NPY after ischemia induction in pigs caused a significant reduction of retinal function, as evaluated by standard and global-flash multifocal ERG. This reduction was accompanied by histological damage, as for instance the reduction of ganglion cells, likely via NPY Y 1 and Y 2 , but not Y 5 receptors [94].…”
Section: Neuropeptide Ymentioning
confidence: 99%